The value of nucleoporin 188 in diagnosis, prognosis and immunoregulation: from pan-cancer analysis to gastric cancer verification - Zhu, Zhengfeng; Peng, Ru; Cai, Huanhuan (Frontiers in Immunology, 2025)
BackgroundNucleoporin 188 (NUP188) is a vital component of the nuclear pore complex that regulates cancer progression, but its role in diagnosis, prognosis, and immunoregulation in pan-cancer remains unclear.MethodsA comprehensive exploration of the value of NUP188 was performed using different platforms and software, including TCGA, HPA, UALCAN, TISIDB, cBioPortal, STRING, GSCALite, cancerSEA databases, and R software. The expression of NUP188 in gastric cancer (GC) was detected by immunohistochemistry. The association between NUP188 and clinicopathologic features was explored, and the predictive value of NUP188 was determined. The effect of NUP188 knockdown on the proliferation, migration, and invasion of GC cells was detected in vitro and vivo.ResultsNUP188 was dysregulated in most human cancers compared to normal tissues with great diagnostic accuracy. The NUP188 expression was associated with molecular subtype, pathologic stage, prognosis, cancer status, and genomic heterogeneity in multiple cancer types. NUP188 was also related to the immune subtype and infiltrating levels of immune cells. The protein level of NUP188 was both upregulated in GC tissues, and was related to HP infection, depth of invasion, distant metastasis, TNM stage, and overall survival of GC patients. NUP188 interference restrained the proliferation, migration, and invasion of GC cells, and inhibited the GC growth in vivo.ConclusionNUP188 plays a potential role in pan-cancer diagnosis and prognosis and may serve as a novel biomarker for tumor immunotherapy.